Morphological and functional changes in the testicles of rats with acetylsalicylic acid poisoning - Koval , D.B.; Levenets , O.O.; Shandra , J.-M.V.; Mykolenko , A.Z. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. One of the most important causes of male reproductive dysfunction is the drug's effect on reproductive function, and salicylates, which are components of many medications, play an important role in this process. Salicylate toxicity poses a serious threat to male reproductive health. However, morphological studies play an important role in understanding the mechanisms of salicylate poisoning and, accordingly, in developing effective methods of prevention and treatment. Objective. To determine the peculiarities of structural changes in the testes and their blood vessels in male white rats under experimental exposure to toxic doses of acetylsalicylic acid. Methods. The experiment was conducted on 42 white male laboratory rats, which were divided into control and experimental groups. The experimental group consisted of 32 white male rats in which chronic poisoning was modeled by daily gastric administration of acetylsalicylic acid. Results. According to the results of the study, it was found that 7 days after the administration of acetylsalicylic acid, certain morphological and functional changes occurred in the testicle of rats, which were based on disorders of organ circulation, manifested in the form of moderate vasoconstriction, against which ischemia occurred, leading to the death of epithelial cells. After 14 days of the experiment, there was a partial compensation of the previously identified changes with signs of normalization of organ blood flow. However, after 21 days, the re-development of certain vascular reactions was characteristic, which consisted of an increase in the tone of arterioles and small arteries with simultaneous thickening of their walls narrowing of the lumen, and a decrease in throughput. Conclusion. According to the results of the studies, it was found that prolonged chronic acetylsalicylic acid poisoning led to certain vascular reactions, which consisted of an increase in the tone of arterioles and arteries with simultaneous thickening of their walls and narrowing of the lumen and a decrease in throughput.